TELAAH FIQH MUAMALAH DALAM AKAD TALANGAN HAJI - Haikal, Haikal; Anha, Radilla; Aulia Rifka, Nurwahda; Kamil, Muh. Ahsan; Kamaruddin, Kamaruddin (Universitas KH. A. Wahab Hasbullah, 2026)
The development of Islamic banking in Indonesia has led to various sharia-based financial products, one of which is the Hajj bailout fund. This product serves as a solution for Muslims who wish to perform the pilgrimage but are constrained by the initial deposit requirement. This study aims to analyze the Hajj bailout contract from a fiqh muamalah perspective, reviewing its compliance with sharia principles and DSN-MUI Fatwa No. 29/DSN-MUI/VI/2002. The method used is a literature study by analyzing academic sources from journals, books, and related fatwas. The results show that the qardh wal ijarah contract is permissible as long as no additional benefits resembling riba are included and administrative fees only cover real costs. From the perspective of maqāṣid al-syarī‘ah, the Hajj bailout provides benefits by facilitating Muslims to perform the fifth pillar of Islam, but it must be maintained to avoid potential harm from excessive debt burdensy. Keywords: Islamic Banking, Hajj Bailout Fund, Fiqh Muamalah, DSN-MUI